Heat Transfer, Volume 1 2002
DOI: 10.1115/imece2002-32941
|View full text |Cite
|
Sign up to set email alerts
|

Nusselt Number Behavior on Deep Dimpled Surfaces Within a Channel

Abstract: Experimental results, measured on a dimpled test surface placed on one wall of a channel, are given for a ratio of air inlet stagnation temperature to surface temperature of approximately 0.94, and Reynolds numbers from 12,000 to 70,000. These data include friction factors, local Nusselt numbers, spatially-resolved local Nusselt numbers, and globally-averaged Nusselt numbers. The ratio of dimple depth to dimple print diameter δ/D is 0.3, and the ratio of channel height to dimple print diameter is 1.00. These r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Because the negative valve, in fact, introducing dimple reduces the loading capacity of journal bearing. This is agreement with the conclusion from Ref [4], it may be the negative effect of dimple.…”
Section: E Influence Ofdimple Densitysupporting
confidence: 94%
See 2 more Smart Citations
“…Because the negative valve, in fact, introducing dimple reduces the loading capacity of journal bearing. This is agreement with the conclusion from Ref [4], it may be the negative effect of dimple.…”
Section: E Influence Ofdimple Densitysupporting
confidence: 94%
“…The lubrication behaviours in the journal/shaft bearing have key influence to its use. In the past, researchers paid more attentions to the study to improve the load capacity of bearing and thermal behaviour by experiment or computational fluid dynamic (CFD) [1] [2][3] [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum heat transfer was observed in the flow-recirculation region inside the dimple. Through experiments, Burgess et al 15 showed the influence of the dimple depth and the dimple imprint diameter on heat transfer, and found that the local and spatially-averaged Nusselt number augmentations increase with an increase in the dimple depth, for various Reynolds numbers from 12,000 to 70,000. Doo et al 16 conducted a parametric study on flows passing through a channel with newly designed surface shapes that comprised of a combination of dimple and riblet.…”
Section: Previous Study Regarding the Application Of Dimple Structurementioning
confidence: 99%
“…Dimples recessed into a flat plane are of interest due to the ability they have in mixing the boundary layer [15][16][17]. Previous numerical work has focused on the dimple flow structure along with some limited flow visualization experiments with which to make com parisons.…”
Section: Case Study 1: Wing Dimplesmentioning
confidence: 99%